The territorial politics of land use planning in Laos - Suhardimana, Diana; Keovilignavong, Oulavanh; Kenney-Lazar, M. (Elsevier, 2019)
This paper examines land use planning processes in Laos, particularly how they are shaped and reshaped by key actors’ interests and strategies across scales and how they are closely interlinked with state logics of territorialization. It critiques dominant perspectives that view land use planning as a tool for bridging policy and institutional divides to generate holistic land governance. Instead, it presents land use planning as a function of power and a contested arena of power struggle, driven primarily by the development targets of sectoral ministries and the interests of powerful local actors. We show how bureaucratic competition and sectoral fragmentation prevail directly within Laos’s National Land Master Plan formulation process. The paper shows how the logics of land governance in Laos are comprised of a disjuncture between national and local land use planning processes and, a disconnect between formal land use planning and actual land use across scales.